Workshop Penjurian Dalam Kompetisi Penulisan Kaligrafi Al Qur’an - Nur Hidayat (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
The purpose of this activity was to improve the calligraphers’ understanding and ability of judging in Al-Qur’an Calligraphy competition which was developed. The subjects of this activity were calligraphers from Gresik East Java. The method that used in this activity was: lecture, question and answer, discussion and practice. The result of this activity showed that the workshop of judging Al-Qur’an calligraphy competition was able to improve the participants’ ability in judging calligraphy, adding the knowledge and applying judgment method in calligraphy competition especially in Musabaqah Khattil Qur’an (Qur’an calligraphy competition).